500 años de la conquista de México : resistencias y apropiaciones (CLACSO, 2022)
In 2021, it will be 500 years since the fall of Mexico-Tenochtitlan, a milestone that marks, in the historical, artistic, literary, and social discourse, the conquest of central Mexico. This book inserts itself into the debate opened by the commemorations and the critical disputes that have been unfolding internationally since the middle of the last decade, and it does so from a Latin American and situated perspective. Aimed at both the specialized reader and a broader audience, this volume intertwines classic readings, innovative approaches to the conquest of Mexico, and reflections on other discourses and representations (visual, material, architectural) that have marked the ways in which this event and its images have been interpreted.